Coupling effects of irrigation amount and fertilization rate on growth and bioactive components of four-year-old licorice (Glycyrrhiza uralensis Fisch) in arid regions of Xinjiang - Abudurezike, Abudukeyoumu; Liu, Xinghong (Frontiers in Agronomy, 2024)
Water scarcity, over-fertilization, and improper crop management practices severely limit the sustainable cultivation of licorice (Glycyrrhiza uralensis Fisch) in the arid regions of Xinjiang. To elucidate the impacts of integrated water and fertilizer management on the growth characteristics and bioactive components (glycyrrhizic acid and liquiritin) of four-year-old licorice plants, a comprehensive four-year field experiment was conducted from 2019 to 2022.The experiment included four irrigation levels (W1: 2500 m³/ha, W2: 4000 m³/ha, W3: 5500 m³/ha, W4: 7000 m³/ha) and four fertilization rates (F1: 305 kg/ha, F2: 610 kg/ha, F3: 915 kg/ha, F4: 1220 kg/ha), following a completely randomized design. Results indicated that both irrigation and fertilization significantly influenced plant height, root length, root weight, root diameter, leaf area index, and root-to-shoot ratio. The optimal growth characteristics were observed under the W2F2 treatment. The contents of glycyrrhizic acid and liquiritin varied significantly among different water and fertilizer treatments, with the highest levels observed under the W2F2 treatment. Excessive irrigation (W4) and over-fertilization (F4) led to a decrease in these bioactive components. A comprehensive evaluation of the growth characteristics and bioactive components revealed that the ideal irrigation and fertilization parameters were 4000 m³/ha and 610 kg/ha, respectively. These parameters optimized plant development and bioactive component accumulation while ensuring efficient resource use. This study provides scientific evidence for optimizing irrigation and fertilization strategies to enhance licorice yield in arid regions, thereby supporting sustainable agricultural practices and improving economic benefits.